Teaching Culture and Developing Cultural Diversity Awareness and Intercultural Communicative Competence in Schools with English as the Medium of Instruction: A Pilot Study - Dogan Ger, Songul (Working Papers in Language Pedagogy, 2022)
The development of cultural diversity awareness (CDA) and intercultural communicative competence (ICC) is recognised as an integral aspect of foreign language teaching and the teaching of linguistic competence due to the inevitable social and cultural connections that stem from globalisation and mobility. Parents who send their children to international schools expect them to become global citizens. Therefore, international schools in which English is used as the lingua franca follow curricula and use teaching materials that can be adapted to the teaching of culture. At the same time, they endeavour to employ teachers who have the experience or flexibility to work with students from different cultures in multicultural settings. The present study explores teachers’ attitudes and practices with respect to the development of CDA and ICC, as well as their students’ responses. The study piloted classroom observation procedures for subsequent use in larger-scale research by the author on the development of CDA and ICC. The pilot study is based on the thematic content analysis of classes in literature and English as an additional language (EAL), observed in an international school in Budapest. The findings reveal that both types of classes included a variety of culture-related activities, although these were mainly limited to English-speaking countries and lacked a critical approach. However, the cultural activities explored and described in the present study can be transferred to the context of the teaching of English as a foreign language (EFL).